Programy postępowania z więźniami jako podstawa resocjalizacji oraz przestrzegania ich praw - Juzl, Miloslav (Kultura-Społeczeństwo-Edukacja, 2013)
The aim of this article is to introduce and explain the core of social rehabilitation of prisoners which lies in creation and e ect of treatment as a necessary prerequisite for their successful return to civic society and as the main factor of permanent humanization of our prison system in the context of respecting the rights and duties of prisoners.